Acetylcholinesterase Biosensor Based on Poly (diallyldimethylammonium chloride)-multi-walled Carbon Nanotubes-graphene Hybrid Film - Sun, Xia; Gong, Zhili; Cao, Yaoyao; Wang, Xiangyou (Nano-Micro Letters, 2013)
In this paper, an amperometric acetylcholinesterase (AChE) biosensor for quantitative determination of carbaryl was developed. Firstly, the poly (diallyldimethy-lammonium chloride) -multi-walled carbon nanotubes-graphene hybrid film was modified onto the glassy carbon electrode (GCE) surface, then AChE was immobilized onto the modified GCE to fabricate the AChE biosensor. The morphologies and electrochemistry properties of the prepared AChE biosensor were investigated by using scanning electron microscopy, cyclic voltammetry and electrochemical impedance spectroscopy. All variables involved in the preparation process and analytical performance of the biosensor were optimized. Based on the inhibition of pesticides on the AChE activity, using carbaryl as model compounds, the biosensor exhibited low detection limit, good reproducibility and high stability in a wide range. Moreover, the biosensor can also be used for direct analysis of practical samples, which would provide a new promising tool for pesticide residues analysis.